Miniaturized Battery-Free Wireless Systems for Wearable Pulse Oximetry - Kim, Jeonghyun (Adv Funct Mater, 2016)
Development of unconventional technologies for wireless collection, storage and analysis of quantitative, clinically relevant information on physiological status is of growing interest. Soft, biocompatible systems are widely regarded as important because they facilitate mounting on external (e.g. skin) and internal (e.g. heart, brain) surfaces of the body. Ultra-miniaturized, lightweight and battery-free devices have the potential to establish complementary options in bio-integration, where chronic interfaces (i.e. months) are possible on hard surfaces such as the fingernails and the teeth, with negligible risk for irritation or discomfort. Here we report materials and device concepts for flexible platforms that incorporate advanced optoelectronic functionality for applications in wireless capture and transmission of photoplethysmograms, including quantitative information on blood oxygenation, heart rate and heart rate variability. Specifically, reflectance pulse oximetry in conjunction with near-field communication (NFC) capabilities enables operation in thin, miniaturized flexible devices. Studies of the material aspects associated with the body interface, together with investigations of the radio frequency characteristics, the optoelectronic data acquisition approaches and the analysis methods capture all of the relevant engineering considerations. Demonstrations of operation on various locations of the body and quantitative comparisons to clinical gold standards establish the versatility and the measurement accuracy of these systems, respectively.